Developing a business plan - Mohd Sam, Mohd Fazli; Md. Taib, Mohd Syafiq; Alias, Siti Nur Aisyah; Mohamed, Nurul Hasyimah (Penerbit UTeM Press, 2025)
A business plan is a detailed outline of the vision of the company. It is a document detailing what you are going to do and how you plan to do it. For those that write and read them, business plans may help perform a variety of activities. Investment-seeking developers are using them to relay their vision to prospective buyers. They may also be used by firms looking to recruit key workers, potential venture opportunities, negotiating with vendors, or even learning how to best run their industries. For multiple reasons, there are numerous business plans, and the best business plans are living documents that respond as easily as possible to real-world conditions.